A computationally efficient nonlinear foil air bearing model for fully coupled, transient rotor dynamic investigations. (January 2021) - Baum, Christoph; Hetzler, Hartmut; Schröders, Simon; Leister, Tim; Seemann, Wolfgang
Abstract: A novel physical and mathematical model of foil air bearings is developed with emphasis on computational time-efficiency for rotor dynamic investigations. The structural model accounts for the nonlinear deformation behavior, assumes linear viscous damping and is directly coupled to the fluid model. Galerkin's method is applied to the non-dimensional model to reduce its dimension and thus its computational costs. The model is validated via published experimental data and the reduction technique by comparing with the unreduced model. The reduction approach decreases the computation time up to a factor 1000, with a slight loss in accuracy (error of 0.01 in average). Finally, the bearing model is coupled with a rigid rotor model to show the applicability during a run-up and coast-down. Highlights: Model order reduction of Reynolds equation for ideal gases with speed up to factor 1000. Nonlinear structure model for foil gas bearings validated with measurement. Holistic coupling method of gas foil bearing and rotor model. Nonlinear, fully coupled run-up and coast-down of simple rotor and foil air bearing model.